Influence of calcined medium grade clay on the properties of Portland cement pastes. Issue 5 (2nd November 2022) - Rakhimova, Nailia R.; Morozov, Vladimir P.; Eskin, Aleksey A.
ABSTRACT: In the recent decades, the composition of Portland cements has undergone significant changes related to an increase in the range and content of supplementary cementitious materials following development of composite and multicomposite cements. The development of these binders that meet the requirements of sustainability requires the expansion and adaptation of the mineral resource base of cement industry to the production of low-emission binders with a gradual decrease of resource and energy intensities. Efforts to find the widespread sources of pozzolans providing high reactivity and physical–chemical stability have led to intensive studies on thermally treated clays of various chemical–mineralogical composition and their industrial adoption. Due to scarcity and high cost of kaolin clays, great attention is given to medium- and low-grade clays. This article reports on a study to evaluate the effect of calcined clay with 52% of clay minerals on the properties of fresh and hardened pastes, in particular on the resistance to sodium sulfate and nitric acid attacks. The reaction products assemblage of the blended Portland cement pastes was investigated by XRD and thermal analyses. The hardened Portland cement pastes incorporated with thermally treated clay demonstrated better durability performance compared to reference ones.